2019
DOI: 10.1021/acs.est.8b05353
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbons Not Declining in Arctic Air Despite Global Emission Reduction

Abstract: Two decades of atmospheric measurements of polycyclic aromatic hydrocarbons (PAHs) were conducted at three Arctic sites, i.e., Alert, Canada; Zeppelin, Svalbard; and Pallas, Finland. PAH concentrations decrease with increasing latitude in the order of Pallas > Zeppelin > Alert. Forest fire was identified as an important contributing source. Three representative PAHs, phenanthrene (PHE), pyrene (PYR), and benzo­[a]­pyrene (BaP) were selected for the assessment of their long-term trends. Significant decline of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(82 citation statements)
references
References 42 publications
2
76
1
3
Order By: Relevance
“…LRAT input, including secondary formation of the derivatives, was more evident in Adventdalen where town emissions influence is reduced. In contrast to the study by Yu et al (2019), no strong indication for LRAT biomass burning emissions was found for this set of air samples. 380…”
Section: Transect Ambient Samplescontrasting
confidence: 99%
See 4 more Smart Citations
“…LRAT input, including secondary formation of the derivatives, was more evident in Adventdalen where town emissions influence is reduced. In contrast to the study by Yu et al (2019), no strong indication for LRAT biomass burning emissions was found for this set of air samples. 380…”
Section: Transect Ambient Samplescontrasting
confidence: 99%
“…2), therefore the presence and diagnostic ratios (Table 3) of these compounds were used as markers of the PP source in the present work. In Yu et al (2019), coal combustion was identified as the main source (68% contribution) of PAHs, at the Zeppelin monitoring station at Ny-Ålesund, Svalbard, and 220…”
Section: Longyearbyen Power Plant Pah Emission Profilementioning
confidence: 99%
See 3 more Smart Citations